Exploring The Impact of Physical Activity and Sleep Quality on Physical Fitness and Cognitive Intelligence - Rifqi Festiawan; Jose Vicente Garcia Jimenez; Muhammad Ashraf Khan; Erwin Oliver Estrella; Bayu Suko Wahono; Fakih Hamdani; Jajang Dede Mulyani (Faculty of Sport and Health Sciences, 2025)
Lifestyle changes and sedentary habits have led to increased health issues, including obesity, cardiovascular diseases, and cognitive decline. This study examines the impact of physical activity and sleep quality on physical fitness and cognitive intelligence among university students. A quantitative correlational design was applied to 60 students aged 19–21 years. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), sleep quality with the Pittsburgh Sleep Quality Index (PSQI), physical fitness through the Multistage Fitness Test (MFT), and cognitive intelligence via the Digit Span Test. Results showed that 58.33% of students engaged in moderate physical activity, and 80% had good sleep quality. Correlation analysis revealed significant relationships between physical activity and physical fitness (r = 0.571, p = 0.002), sleep quality and physical fitness (r = 0.735, p = 0.000), physical activity and cognitive intelligence (r = 0.520, p = 0.004), and sleep quality and cognitive intelligence (r = 0.674, p = 0.001). Regression analysis indicated that sleep quality contributed 33.2% to physical fitness and 28.7% to cognitive intelligence, while physical activity contributed 32.7% and 25.4%, respectively. These findings highlight the need to promote physical activity and sleep hygiene to enhance students’ health.